2022
DOI: 10.3390/jcm11041087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcutaneous Vagus Nerve Stimulation in Erosive Hand Osteoarthritis: Results from a Pilot Trial

Abstract: Beyond its effect on vegetative functions, the activation of the vagus nerve inhibits inflammation and reduces pain signaling. The aim of this open-label pilot study was to determine the efficacy and tolerance of transcutaneous auricular VNS (taVNS) on erosive hand osteoarthritis (EHOA) symptoms. Symptomatic EHOA patients with hand pain VAS ≥ 40/100 mm and ≥1 interphalangeal swollen joint(s) were included. The taVNS was performed for 4 weeks using an auricular electrode applied one hour per day and connected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
0
13
0
3
Order By: Relevance
“…1 -und Kontrolle), Stimulationsparameter, Behandlungsdauer, primäre und sekundäre Ergebnisse sowie beobachtete unerwünschte Ereignisse. [30,40,41,49,53,64,69], n = 154), Migräne (4 Studien [24,39,70,84], n = 133), Rückenschmerz (4 Studien [39,65,66,71], n = 192), rheumatoide Arthritis (RA)/Osteoarthritis (2 Studien [17,46]; n = 45), Fibromyalgie/ systemischer Lupus Erythematodes (SLE) (3 Studien [5,43,79], n = 51), Chemotherapie-induzierte periphere Neuropathie (1 Studie [62]; n = 58), unspezifischer chronischer Schmerz (1 Studie [30], n = 3). Von diesen waren 9 Studien [5,40,41,43,65,66,69,70,84] Schmerz auf einer Visuellen Analogskala (VAS) oder Numerischen Rating-Skala (NRS), psychisches Wohlbefinden und Verträglichkeit/Sicherheit der Stimulation waren die häufigsten primären und sekundären Endpunkte.…”
Section: Materials Und Methodenunclassified
See 1 more Smart Citation
“…1 -und Kontrolle), Stimulationsparameter, Behandlungsdauer, primäre und sekundäre Ergebnisse sowie beobachtete unerwünschte Ereignisse. [30,40,41,49,53,64,69], n = 154), Migräne (4 Studien [24,39,70,84], n = 133), Rückenschmerz (4 Studien [39,65,66,71], n = 192), rheumatoide Arthritis (RA)/Osteoarthritis (2 Studien [17,46]; n = 45), Fibromyalgie/ systemischer Lupus Erythematodes (SLE) (3 Studien [5,43,79], n = 51), Chemotherapie-induzierte periphere Neuropathie (1 Studie [62]; n = 58), unspezifischer chronischer Schmerz (1 Studie [30], n = 3). Von diesen waren 9 Studien [5,40,41,43,65,66,69,70,84] Schmerz auf einer Visuellen Analogskala (VAS) oder Numerischen Rating-Skala (NRS), psychisches Wohlbefinden und Verträglichkeit/Sicherheit der Stimulation waren die häufigsten primären und sekundären Endpunkte.…”
Section: Materials Und Methodenunclassified
“…In 8 Studien [17,24,49,62,65,66,70,71] wurde der Bedarf an Schmerzmit-teln erhoben. In 6 dieser Studien (davon 3 bei chronischem Rückenschmerz und 1 bei chronischer Migräne) [49,62,65,66,70,71] konnte die Schmerzmitteleinnahme in der aVNS-Gruppe reduziert werden.…”
Section: Ergebnisseunclassified
“…There was a significant reduction in NPRS score after 1 week of stimulation (P < 0.001), after 2 weeks of stimulation (P < 0.001), and after 3 weeks of stimulation (P < 0.001). 26 A study was conducted by Courties et al about the effect of tVNS on hand osteoarthritis. Eighteen patients who fulfilled the American College of Rheumatology (ACR) criteria of hand osteoarthritis received tVNS located in cymba conchae, 1 h/day at 25 Hz, intensity increased gradually with patient tolerance, and pulse width 50 μs for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In an open-label pilot study, we showed that 1-hour auricular tVNS per day significantly decreased pain and the number of tender and swollen joints and improved function in 18 patients with EHOA, but more importantly was well tolerated 28. However, the low number of patients and no control group could not allow us to rule out a placebo effect for effectiveness.…”
Section: Introductionmentioning
confidence: 87%